E-PORTFOLIO: BEST PRACTICE FOR DEVELOPING LISTENING COMPREHENSION SKILL - Aytimbetova U.T. (Research Focus International Scientific Journal, 2025)
The most information is perceived by listening, thus it is important to develop particularly foreign language learners. It is known that any learner is to be bored when he\she listens more. Thus, it needs an effective way of teaching to improve students’ listening comprehension skill. The present study investigates using e-portfolios in improving listening skill of university students and examines the effectiveness of the use of e-portfolios in the teaching of listening by observing students’ listening in the classroom.